PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN PADA MTS NEGERI 3 KOTA JAMBI - Imam Rofi’i (Pusat Riset dan Inovasi Nasional, 2022)
Library information systems in this age of technology are indispensable in providing services and meeting every demand of the staff and management. The integration of databases, the use of electronic equipment, these computerized processes are often referred to as library automation. Library automation is a process of managing libraries using information technology. This automation process then presents the concept of a library system. Currently there are several schools whose libraries still use manual systems. Where the process of managing data on borrowing and returning books is still applied manually so that it experiences obstacles such as errors, difficulties in finding data and making reports to the head of the library. The purpose of this study is to produce a design of a library information system to facilitate the management of data in the library. This library information system is built with the waterfall method with five stages of applicable methods, namely software needs analysis, system design, program creation, system testing, and maintenance with PHP programming language and MySql as the database. System modeling is created using use case diagrams, activity diagrams, and class diagrams. Conclusions that can be drawn in this study include, this study produced a library information system that can manage data automatically and can print reports needed by the head of the library .The system can also automatically calculate the fines to be paid by members who are late in returning books.